A comprehensive catalog of LncRNAs expressed in T-cell acute lymphoblastic leukemia. Issue 8 (3rd July 2019) - Kermezli, Yasmina; Saadi, Wiam; Belhocine, Mohamed; Mathieu, Eve-Lyne; Garibal, Marc-Antoine; Asnafi, Vahid; Aribi, Mourad; Spicuglia, Salvatore; Puthier, Denis
Abstract: Several studies have demonstrated that LncRNAs can play major roles in cancer development. The creation of a catalog of LncRNAs expressed in T cell acute lymphoblastic leukemia (T-ALL) is thus of particular importance. However, this task is challenging as LncRNA expression is highly restricted in time and space manner and thus may greatly differ between samples. We performed a systematic transcript discovery in RNA-Seq data obtained from T-ALL primary cells and cell lines. This led to the identification of 2560 novel LncRNAs. After the integration of these transcripts into a large compendium of LncRNAs ( n = 30478) containing both known LncRNAs and those previously described in T-ALLs, we then performed a systematic genomic and epigenetic characterization of these transcript models demonstrating that these novel LncRNAs share properties with known LncRNAs. Finally, we provide evidence that these novel transcripts could be enriched in LncRNAs with potential oncogenic effects and identified a subset of LncRNAs coregulated with T-ALL oncogenes. Overall, our study represents a comprehensive resource of LncRNAs expressed in T-ALL and might provide new cues on the role of lncRNAs in this type of leukemia.